Harry by the sea. - Zion, Gene.; Graham, Margaret Bloy (New York, Harper & Row, 1965)
When a wave washes over a dog and covers him with seaweed, he is mistaken for a sea monster.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
3.4
K-3
Keywords: Seashore -- Fiction; Dogs -- Fiction; Dogs -- Fiction